2020
DOI: 10.1039/d0ta07644a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron sputtering enabled synthesis of nanostructured materials for electrochemical energy storage

Abstract: Batteries and supercapacitors are promising candidates for electrochemical energy storage while the development of their electrode materials is becoming a bottleneck. This limitation necessitates the design of high specific capacity/capacitance,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 252 publications
0
12
0
Order By: Relevance
“…The physical methods present general and simple strategies to synthesize highly pure and doped MN. The most common examples of physical methods of synthesis include physical vapor deposition (PVD) [ 46 , 47 ] and plasma/laser-based methods [ 48 ]. However, the development of multiple hybrids with different morphologies and porosities through physical methods is challenging.…”
Section: Synthesis Of Mnsmentioning
confidence: 99%
“…The physical methods present general and simple strategies to synthesize highly pure and doped MN. The most common examples of physical methods of synthesis include physical vapor deposition (PVD) [ 46 , 47 ] and plasma/laser-based methods [ 48 ]. However, the development of multiple hybrids with different morphologies and porosities through physical methods is challenging.…”
Section: Synthesis Of Mnsmentioning
confidence: 99%
“… 26 29 The electrode–electrolyte interface is stabilized by depositing a coating layer on the electrode surface to reduce the interface impedance. 30 It was reported that Al 2 O 3 coating can significantly improve the electrochemical performance of LCO films. 31 , 32 Woo et al 33 coated Al 2 O 3 on the surface of a LiCoO 2 positive electrode and found that the Al 2 O 3 coating layer can effectively inhibit the interdiffusion between LiCoO 2 and the solid electrolyte and reduce the increase in interfacial impedance during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we examined Pt1-x-Tax thin film catalysts produced by co-sputtering. The sputter-deposition method is well known for its potential in the synthesis of nanomaterials for electrochemical catalysts [16,17]. It allowed us to prepare the catalyst with platinum and tantalum in any desired ratio on a various of substrates.…”
Section: Introductionmentioning
confidence: 99%